Iter progettuali ed estensioni di campo. Una conversazione tra Giampaolo Proni e Raffaella Trocchianesi - Lambertini, Anna (Ri-Vista. Research for landscape architecture, 2015)
A semiologist and a designer dialog about metaplanning, creative processes to realize new products and therefore about concept, design models and maps, cleverly using reflections riched in their own fields of research. This interdisciplinary contribution is so important for landscape planners that we asked Giampaolo Proni to present us his recent interview to Raffaella Trocchianesi about the rela- tionship between semiotic and design: Hypertextual Landscapes is the result.